An Investigation of Bilateral Symmetry in Softball Pitchers According to Body Composition - Kenzie B. Friesen; Kenzie B. Friesen; Angelica E. Lang; Karen E. Chad; Gretchen D. Oliver (Frontiers Media S.A., 2022)
IntroductionHigh body fat percentage (bf%) is considered a potential injury risk factor for softball pitchers amidst the already high rates of pitching-related injury. Similarly, research points out that large bilateral asymmetries are another risk factor for softball pitchers. As softball pitching is a highly asymmetric sport and the repetitive nature of the windmill pitch places high stress on the body while pitchers are in unbalanced and asymmetric positions, research examining body composition and asymmetry is necessary.PurposeThe purpose of this study was to compare functional characteristics of softball pitchers with a healthy and a high bf%. Bilateral symmetry was assessed for pitchers' hip and shoulder isometric strength (ISO) and range of motion (ROM) between the following two groups of softball pitchers: (1) those with a high bf% (≥32%) and (2) those with a healthy bf% (<32%).MethodsA total of 41 high school female softball pitchers from the southern United States agreed to participate (1.69 ± 0.07 m, 76.14 ± 17.08 kg, 15.1 ± 1.1 years). Pitchers completed a dual-energy X-ray absorptiometry (DEXA) scan and were grouped into one of the following two categories based on their bf%: healthy (<32 bf%) and high (≥32 bf%). Bilateral symmetry was assessed for pitchers' hip and shoulder ISO and ROM using a handheld dynamometer and inclinometer, respectively. Bilateral arm bone and lean mass was also measured via the DEXA.ResultsMixed analyses of variance revealed a significant interaction between bf% groups and side dominance for internal rotation shoulder ROM, F(1, 39) = 14.383, p < 0.001, η2p = 0.269. Main effects for side dominance were also observed for shoulder external rotation ISO, F(1, 39) = 8.133, p = 0.007, η2p = 0.173, hip internal rotation ISO, F(1, 39) = 4.635, p = 0.038, η2p = 0.106, arm bone mass, F(1, 39) = 38.620, p < 0.001, η2p = 0.498, and arm lean mass, F(1, 39) = 101.869, p < 0.001, η2p = 0.723.ConclusionAsymmetries and slight differences in functional characteristics exist between bf% groups. Altered functional characteristics may influence pitchers' windmill pitch movement and should be acknowledged by support staff to improve softball pitchers' health and longevity.ImplicationsInsight into asymmetries can help researchers and clinicians understand the implication of excess body fat and further theorize mechanisms of injury among this athlete population.